Vasorelaxant Effect of a Newly Synthesized Dihydropyridine Ethyl Ester (DHPEE) on Rat Thoracic Aorta: Dual Mechanism of Action - Hossein Babaei; Farzaneh Ebrahimi; Javid Shahbazi Mojarrad; Yadollah Azarmi; Afsaneh Gharehbagheri (Tabriz University of Medical Sciences, 2011)
Introduction: DHPEE is a newly synthesized compound by merging the key structural elements in an angiotensin receptor blocker (Telmisartan) with key structural elements in 1,4- dihydropyridine calcium channel blocker (Nifedipine). In this study, we examined dual calcium channel blocking and AT1 antagonist activity for DHPEE. Methods: The functional inhibitory characteristics of DHPEE were studied in vitro in rat thoracic aorta preparations precontracted by phenylephrine (1µM) or KCl (80µM) or Ang II in normal or calcium-free solutions. Results: Concentration-dependent significant relaxation was observed in aortic rings precontracted with phenylephrine, KCl or Ang II. The tension increment produced by increasing external calcium was also reduced by DHPEE. DHPEE caused a marked decrease in the maximal contractile response of the vasoactive agents and shifted their concentration-response curves to the right. Conclusion: DHPEE possesses dual characteristics and cause vasorelaxation by blocking the L-type calcium channels and blocking Ang II receptors (AT1) in rat aortic smooth muscle.